The Influence of Income on Generation Z Investment Decisions in South Jakarta - Andini Andini; Sri Astuti; Moh. Supendi (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines the influence of personal income on investment decisions among Generation Z in South Jakarta, situating the analysis within a growing body of global research that links financial capacity to the investment behavior of young people. While prior work has documented that higher income levels increase risk-taking and portfolio diversification among young adults, little is known about this phenomenon in the Indonesian context. Guided by behavioral finance theory and the Theory of Planned Behavior, we adopt a quantitative design with 101 purposively selected respondents, collecting data through an online questionnaire. Simple linear regression, Spearman correlation, and ordinal regression (SPSS v30) reveal a strong positive relationship between monthly income and investment decision intensity (r = 0.669, p 0.001), with income accounting for 98.7% of the explained variance in the ordinal model.